Comparing the Language Learning Strategies (LLS) employed by English As A Second Language (ESL) learners and the perception of english language teachers on their students’ use of lls at UiTM Dungun / Muhmad Noor Wan Chik, Badariah Sani & Ahmad Nawir Abu Amrin - Wan Chik, Muhmad Noor; Sani, Badariah; Abu Amrin, Ahmad Nawir (2006)
This study aimed at exploring the types of Language Learning Strategies employed by undergraduate students and comparing them with their teachers’ or lecturers’ perceptions of what Language Learning Strategies they used. 200 undergraduate students from 5 different programs and 10 lecturers were chosen as samples. Data from students were gathered by using the Strategy Inventory for Language Learning (SILL) for ESL/EFL developed by Oxford (1989) while data from the lecturers were collected using a modified version of the SILL. Results concerning Language Learning Strategies used by students were discovered and compared with the lecturers’ perceptions of their students’ Language Learning Strategies usage. Findings revealed that students used only a limited number of Language Learning Strategies when they used or learnt the English Language and at a moderate level. A significant difference was found between the Language Learning Strategies used by the students and the teachers’ or lecturers’ perceptions of students’ Language Learning Strategies used. The researchers contended that the varied and plentiful usage of the Language Learning Strategies can improve students’ second language acquisition. Some suggestions on the use of Language Learning Strategies were given.